2009
DOI: 10.1890/08-1207.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting declines in avian species richness under nonrandom patterns of habitat loss in a Neotropical landscape

Abstract: Abstract. One of the key concerns in conservation is to document and predict the effects of habitat loss on species richness. To do this, the species-area relationship (SAR) is frequently used. That relationship assumes random patterns of habitat loss and species distributions. In nature, however, species distribution patterns are usually nonrandom, influenced by biotic and abiotic factors. Likewise, socioeconomic and environmental factors influence habitat loss and are not randomly distributed across landscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 81 publications
2
10
0
5
Order By: Relevance
“…These are the mechanisms that are altered once a threshold is passed and that explain the short-or long-term decline of the population. Several recent studies (Betts et al 2006, Rompré et al 2009) have shown that thresholds do indeed exist for species with large home ranges, which confirms predictions made using models (Lande 1987;Andrén 1994;Andrén et al 1997;With and King 1999;Fahrig 2001Fahrig , 2003. In forest environments, regardless of the type of forest, habitat loss is defined as a decrease in the area occupied by the forest type.…”
Section: Definitionssupporting
confidence: 60%
See 4 more Smart Citations
“…These are the mechanisms that are altered once a threshold is passed and that explain the short-or long-term decline of the population. Several recent studies (Betts et al 2006, Rompré et al 2009) have shown that thresholds do indeed exist for species with large home ranges, which confirms predictions made using models (Lande 1987;Andrén 1994;Andrén et al 1997;With and King 1999;Fahrig 2001Fahrig , 2003. In forest environments, regardless of the type of forest, habitat loss is defined as a decrease in the area occupied by the forest type.…”
Section: Definitionssupporting
confidence: 60%
“…The scientific literature describes two types of thresholds, the first refers to one or more species populations affected by habitat loss (Andrén 1994, With and King 1999, Fahrig 2003, while the second, more recently described, concerns the number of species (species richness) affected by a loss in habitat (Radford et al 2005, Rompré et al 2009). …”
Section: The Foundations Of the Critical Habitat Threshold Conceptmentioning
confidence: 99%
See 3 more Smart Citations